They Who Hesitate: The Influencing Factors of Hesitation Phenomena in Students’ Speaking at IAIN Langsa - Keane Mariza Ajani (JADEs Journal of Academia in English Education, 2022)
This research is carried out to investigate the influencing factors of the Hesitation phenomena in students’ speaking. The participant of this research is five students of seventh semester from English Department of IAIN Langsa in academic Years 2017-2021 who have been selected through purposive sampling based on certain characteristics. This research used qualitative method to gain the data, observation and interview. Based on the results, there are five factors lead the students to hesitate during speaking, which is breathing, pragmatic reason, cognitive process, linguistic planning, and nervousness. Therefore, one of the participants blamed that breathing can be the solution to overcome hesitation in speaking as well as practice and preparation. The researcher has several suggestions for this research. Specifically, first, the students should be aware of the existence of the hesitation phenomena during their speaking. Second, it is necessary to raise the lecturers' awareness since the hesitation phenomenon is an important factor that affects students speaking performance and difficulty. Finally, due to the limitation of this study, further investigation hopes to explore more with a larger population and different groups of students. Therefore, further research about certain approaches or methods to reduce hesitation phenomena in speaking is needed.